Gendered perspectives of yoga in the Key Stage 1 classroom: Qualitative content analysis indicates contrasting views of teachers and pupils - Katie Wilkin; Claire Thornton; Georgia Allen-Baker (PLoS ONE, 2026)
The gendering of physical activities is ubiquitous, with those involving strength, endurance, and physical contact considered masculine, and those involving concentration, presentation, and flexibility considered feminine. Yoga, for instance, tends to be regarded by adults and adolescents as a feminine activity for women/ girls, however, it is not known whether younger children share this view. Using data from six individual teacher interviews and a child-friendly task with 23 pupils (working in four separate groups), qualitative content analysis (QCA) was used to identify and explore the gendered perspectives of yoga held by Key Stage 1 teachers and pupils in schools across the North East of England. Data were considered according to Gender Schema Theory (GST) and indicate that, although young pupils seem to hold no consensus view of yoga being a female/ feminine activity, teachers observe reluctance from some of their male pupils during yoga activities in school. As previous research has revealed that teachers generally expect male pupils to be more competitive than their female peers, the findings are discussed in relation to the non-competitive nature of yoga.